2007
DOI: 10.1053/j.gastro.2007.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids Ameliorate Pain and Reduce Disease Pathology in Cerulein-Induced Acute Pancreatitis

Abstract: Background & Aims-The functional involvement of the endocannabinoid system in modulation of pancreatic inflammation, such as acute pancreatitis, has not been studied to date. Moreover, the therapeutic potential of cannabinoids in pancreatitis has not been addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 22 publications
8
80
1
Order By: Relevance
“…The mRNA extraction, cDNA synthesis and QRT-PCR were performed as described previously (specimens used: normal n ¼ 19; PDAC n ¼ 57) (Michalski et al, 2007a). Data are presented as relative expression fold.…”
Section: Qrt-pcrmentioning
confidence: 99%
“…The mRNA extraction, cDNA synthesis and QRT-PCR were performed as described previously (specimens used: normal n ¼ 19; PDAC n ¼ 57) (Michalski et al, 2007a). Data are presented as relative expression fold.…”
Section: Qrt-pcrmentioning
confidence: 99%
“…p38 and JNK have been described to become activated by CB 1 and CB 2 in cells of hippocampus in mice (11,13). Recently, a study showed that CB 1 and CB 2 are also expressed on pancreatic cells and that the relatively nonselective CB 1 /CB 2 agonist HU210 ameliorates acute experimental pancreatitis (42). Anti-inflammatory effects of cannabinoids and components of the endocannabinoid system (ECS) have also been described in other models.…”
mentioning
confidence: 99%
“…Our study might suggest that compounds capable to prolong the lifespan of anandamide by inhibiting its inactivation, and that have proved useful in several animal models of pain, inflammation, and itch (15,16,(41)(42)(43)(44)(45)(46)(47)(48), might not be necessarily suitable for the symptomatic treatment of candidiasis, as they might also promote the formation of 3-HAEA, a likely algogenic compound. Furthermore, our data provide an unusual example of the typical capability of pathogenic microorganisms to control, or even exploit, innate defense mechanisms to facilitate infection (49,50).…”
Section: Discussionmentioning
confidence: 98%
“…TRPV1 sensitization likely occurs during candidiasis, because increased expression of vulvar TRPV1 receptors is observed during vulvodynia, a condition similar to that caused by candidiasis (14), and clotrimazole, a widely used antimycotic agent, was suggested to owe its inflamma- tory and algogenic side effects to its capability to activate TRPV1 receptors (40). On the other hand, several peripheral inflammatory conditions causing pain and/or itch are known to be accompanied by elevated levels of anandamide as an adaptive reaction to counteract these symptoms, as suggested by the observation that compounds that prolong the life span of anandamide by inhibiting its inactivation exert anti-inflammatory effects (15,16,(41)(42)(43)(44)(45)(46)(47). Thus, it seems reasonable to hypothesize that, during candidiasisinduced inflammation, on the one hand TRPV1 is sensitized, and, on the other hand, anandamide is produced by host or neighboring cells.…”
Section: Discussionmentioning
confidence: 99%